Photocathode device using diamondoid and cesium bromide films - Clay, William A.; Maldonado, Juan R.; Pianetta, Piero; Dahl, Jeremy E. P.; Carlson, Robert M. K.; Schreiner, Peter R.; Fokin, Andrey A.; Tkachenko, Boryslav A.; Melosh, Nicholas A.; Shen, Zhi-Xun; Justus Liebig University Giessen (My University, 2012)
A photocathode structure is presented that shows promise for use in high brightness electron sources. The structure consists of a metal substrate, a monolayer of a diamondoid derivative, and a thin film of cesium bromide. Diamondoid monolayers reduce the energy spread of electron emitters, while cesium bromide increases the yield and stability of cathodes. We demonstrate that the combined structure retains these properties, producing an emitter with lower energy spread than the corresponding cesium bromide emitter (1.06?eV versus 1.45?eV) and higher yield and stability than un-coated diamondoid emitters.
Keywords: caesium compounds; monolayers; organic compounds; photocathodes; thin film devices; thin films; ddc:530